Design gráfico da pluma de contaminação por compostos orgânicos voláteiss utilizando software CAD na investigação de passivo ambiental em um posto revendedor de combustíveis em Natal/RN - Aquino Sobrinho, Hercules Lisboa de (2011)
Among the potentially polluting economic activities that compromise the quality of groundwater are the gas stations. The city of Natal has about 120 gas stations, of which only has an environmental license for operation. Discontinuities in the offices were notified by the Public Ministry of Rio Grande do Norte to carry out the environmental adaptations, among which is the investigation of environmental liabilities. The preliminary and confirmatory stages of this investigation consisted in the evaluation of soil gas surveys with two confirmatory chemical analysis of BTEX, PAH and TPH. To get a good evaluation and interpretation of results obtained in the field, it became necessary three-dimensional representation of them. We used a CAD software to graph the equipment installed in a retail service station fuel in Natal, as well as the plumes of contamination by volatile organic compounds. The tool was concluded that contamination is not located in the current system of underground storage of fuel development, but reflects the historical past in which tanks were removed not tight gasoline and diesel